The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5897/jece2019.0458
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal assessment of the physico-chemical properties of surface water and sediments in the vicinity of a scrap metal recycling industry in Southwestern Nigeria

Abstract: The study assessed the seasonal variations in the physico-chemical properties of surface water and sediments in some villages located around a scrap metal recycling industry in Ile-Ife. This is with a view to monitor the impact of the industry on the quality of surrounding water. The three water bodies (one river, one stream and one pond) identified in the area were sampled every other month for ten months. Water and sediment were sampled from the water bodies and their physico-chemical properties were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(12 reference statements)
1
2
0
Order By: Relevance
“…The mean concentration of Ca 2+ is highest in pond 1 (0.112±0.032) mgkg -1 and lowest in pond 3 (0.065±0.018) mgkg -1 while the mean concentration of K + is highest in pond 3 (0.781±0.296) mgkg -1 and lowest in pond 2 (0.411±0.142) mgkg -1 within the sampling locations. The values of the ions obtained in the study are generally high in the pond which is in accordance with the report of Okoya et al (2020b) in a similar study but different locations.…”
Section: Sediment Samples Analysissupporting
confidence: 92%
“…The mean concentration of Ca 2+ is highest in pond 1 (0.112±0.032) mgkg -1 and lowest in pond 3 (0.065±0.018) mgkg -1 while the mean concentration of K + is highest in pond 3 (0.781±0.296) mgkg -1 and lowest in pond 2 (0.411±0.142) mgkg -1 within the sampling locations. The values of the ions obtained in the study are generally high in the pond which is in accordance with the report of Okoya et al (2020b) in a similar study but different locations.…”
Section: Sediment Samples Analysissupporting
confidence: 92%
“…It is fascinating to observe that these values align with the recommended limit of 200 mg/L and 600 mg/L as CaCO3 set by regulatory bodies[50,51,53]. These results are consistent with other studies conducted in the south-western region of Nigeria, which reported acidity values ranging from 5.0 mg/L to 12.0 mg/L as CaCO3 and alkalinity values ranging from 33.3 mg/L to 78.60 mg/L as CaCO3[60]. Further emphasizing the reliability of these findings, the control point exhibited an acidity value of 47.63 mg/L as CaCO3 and an alkalinity value of 44.69 mg/L as CaCO3, both falling well below the limits recommended by the regulatory bodies (see Table2).…”
supporting
confidence: 91%
“…Preparation and sampling of wastewater: The water sampling bottles (2.5 L) were pre-cleaned according to standard methods for organic contamination sampling 13,14 . To prevent further contamination, the bottles were allowed to air dry for 24 hrs and the mouthparts were wrapped in aluminium foil until sampling.…”
Section: Characterization Of Sawdust Activated Carbon (Sac)mentioning
confidence: 99%